@GBeau I think that we could prove it as follows.
$s_n\rightarrow\infty\implies (s_n)^2\rightarrow\infty$
We know that $s_n \to +\infty$. That means that $\forall M>0, \exists n_0 \in \mathbb{N} $ such that $\forall n \geq n_0: s_n>M$
$s_n^2-k^2=(s_n-k)(s_n+k)$ where $k$ any positive integer.
From the above definition, $\exists n_0$ such that $\forall n \geq n_0$: $s_n>k \Rightarrow s_n-k>0$.
Also
since $s_n \to +\infty$ we have that $s_n >0 \text{ for some } n \geq n_1$ and so it holds that $s_n+k>0 \Rightarrow s_n>-k,k>0$ for $n \geq n_1$.